Governance Indicators and Responsiveness to Population Decline: School Closures in Practice and Discourse in Saxony-Anhalt - Bartl, Walter; Sackmann, Reinhold (Comparative population studies, 2016)
The subject of this analysis is the practice of school closures, since it constitutes a key response to demographic decline and is usually hotly disputed in regional discussions on demographic change. Our research is guided by two questions: How do political and administrative responses to demographic decline emerge? How is the practice of school closure publicly portrayed and discussed in the newspapers? We assume that in democratic welfare regimes, the spatial allocation of school infrastructures is mediated by the use of key administrative indicators allowing the calculation and public deliberation of questions related to education infrastructure policy. However, in transformation societies, a democratic political culture of "governing by numbers" only develops as a result of collective learning processes in which the participants acquire what we refer to as "democratic numeracy". In the stratified German school system, social prestige is conferred unequally among the different school types, with the grammar school (Gymnasium) being the most prestigious school type. It is therefore likely that the elements of the school system are not affected equally by policy responses to demographic decline and public attention, which results in spatial inequalities. Empirically, the article follows a mixed-methods approach, whilst emphasising a quantitative and qualitative content analysis of school closures in the regional press of Saxony-Anhalt from 1990 to 2014. The results show that, in the transformation process, the relevance of indicator-based governance of the school infrastructure increases both in practice and in discourse. However, as the participants gain in democratic numeracy, the use of numbers becomes politicised. With respect to the pattern of school closures, grammar schools receive a disproportionately large share of public attention. This has a positive effect on their survival chances and diminishes differences in spatial distances between grammar schools and integrated secondary schools.